Drying temperature affects Mentha spicata, Salvia officinalis, and Thymus vulgaris quality, essential oil yield, composition and biocidal properties - Xylia, Panayiota; Chrysargyris, Antonios; Kyriakou, Kalia; Miltiadous, Panagiota; Tzortzakis, Nikos G. (My University, 2025)
Drying is a well-recognized procedure for the preservation of medicinal and aromatic plants, however each species responds differently to drying conditions. The current study evaluated the impacts of drying temperatures (i.e. 20, 35, 42, and 49 °C) on the quality of dried spearmint ( Mentha spicata ), sage ( Salvia officinalis ), and thyme ( Thymus vulgaris ) and their essential oils content, composition and biocidal characteristics (antioxidant, antibacterial, and cytotoxic). The results indicated that faster moisture loss and a darker product were observed with higher drying temperatures (i.e. 49 °C). High drying temperatures consumed lower energy and produced less carbon dioxide due to the shorter oven operation time. For spearmint, drying at 35 and 42 °C resulted into essential oils rich in carvone which also presented good antioxidant and antibacterial activity. For sage, drying temperature ranged from 20 to 42 °C, produced high quality oils rich in α -thujone with good antibacterial and antioxidant activities. Drying thyme at temperatures lower than 49 °C (especially 42 °C) resulted into oils rich in thymol, p -cymene and γ -terpinene. These observations are further supported by the increased antioxidant, antibacterial and anticancer activity of the produced thyme oils. The examined thyme essential oils revealed great cytotoxic activity in both female-derived cancer cells (breast-MDA-MB-231 and ovarian-SkoV-3) compared to spearmint and sage oils. The current findings suggest that each plant species responded differently to various drying temperatures and thus the optimization of the drying parameters for each one is important to produce high-quality dried products as well as oils with great biological activities.
Keywords: Biological properties; Medicinal Plants; Drying method; Energy utilization; Spearmint; Thyme